Trace elements in solutions from zeolite synthesis = Pierwiastki śladowe w roztworach po syntezie zeolitów - Adamczyk, Zdzisław; Makosz, Ewa; Nowińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the content of selected elements in solutions formed after the synthesis of zeolitic material based on fly ash. Fly ash samples were taken from two pulverized fuel-fired boilers at the Rybnik Power Plant: one boiler fired solely with coal and one co-fired with coal and biomass.
Keywords: zeolity; ierwiastki śladowe; synteza; popioły lotne; zeolites; trace elements; synthesis; solutions